A Rare Case of Bipolar Clavicle Fracture - Matthew A. Yalizis; Gregory A. Hoy; Eugene T. H. Ek (Case Reports in Orthopedics)
Segmental or bipolar fractures of the clavicle generally refer to a concomitant ipsilateral distal clavicle and midshaft clavicle fracture. These injuries are exceedingly rare and are generally secondary to higher energy injuries. We report a case of a 38-year-old male who sustained a left bipolar clavicle fracture after falling from a push bike while riding recreationally which unusually involved the medial and lateral ends of the clavicle and not the midshaft as previously reported in other patients. The patient’s exact fracture configuration was not immediately apparent highlighting the need for careful examination of the whole clavicle in order to not miss a bipolar fracture.